A Brief Analysis of the Way That Folk Art is Integrated into Cultural Creation Design - Jiang, Jie; Mao, Mengping; Li, Guorui (Journal of Theory and Practice of Social Science, 2023)
In the traditional culture handed down in Our country, folk culture is also an important part, folk art is the product of folk culture, but also the ancestors through continuous efforts and research and handed down the national treasure. Wen gen design is a design idea in the new period, and both the differences between folk art and culture and design, also has the characteristics of the mutual crisscross, in this paper, the folk art into and analyzes the significance of design, so as to take effective fusion strategy for fusion between the two, so as to enhance the connotation of modern culture and design, at the same time make folk art heritage effectively.